Maternal outcome in pregnancy with sickle cell trait haemoglobinopathie - Thakor, Rutvi R.; Patel, Falguni B.; Chaudhary, Minal; Shrivastava, Anjani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Sickle cell trait, the heterozygous state for sickle cell disorders (SCD), which is associated with various obstetrical and non- obstetrical complication. Our objective was to study the pregnancy outcome in women with sickle cell trait. Methods: A prospective observational study was conducted collecting data from medical records of around 40 consecutive consenting subjects admitted in a tertiary health care center of south Gujarat over a period of May 2020 to April 2021 after Human Research Ethics Committee (HREC) approval. Results: In our study majority of the subjects (52.5%) belonged to age group of 18-25 years, majority (62.5%) of subjects were belonged to tribal population. Majority (92.5%) of subjects in our study diagnosed as sickle cell trait post -conceptional. 67% of subjects had various antenatal maternal morbidity among them anemia (45%); preterm labour (12.5%); hypertensive disorder (7.5%) and respiratory failure (2.5%). 65% of our subjects were delivered vaginaly. 5% of subjects had post- partum complication. Conclusions: Though sickle cell trait is considered as a low risk factor during pregnancy, expansion of SCT screening and educational efforts, the availability of reproductive technologies, and the increasing research on clinical complications of SCT have important implications for reproductive and genetic counselling guidelines.